Logical Reasoning in Management: From "Philosopher Kings" to Logical Managers? - Mohid Farooq Butt (Junior Management Science (JUMS), 2023)
To what extent does a manager's logical reasoning ability impact their managerial responsibility? This study delves into the significance of logical reasoning ability in the realm of management. To accomplish this objective, I developed a logical reasoning assessment whose internal consistency was confirmed. Subsequently, I conducted an online survey with a sample of 83 managers (Mage = 39.6; SDage = 11.77). The econometric model (R2 adj = 0.431) revealed a cubic relationship, indicating an influence that logical reasoning ability might have on management responsibility. Notably, managers who pursued formal science education exhibited the highest proficiency in logical reasoning. Conversely, neither age nor GPA exhibited any significant correlation with logical reasoning ability among managers. A comparative analysis of managers' logical reasoning performance against previous studies involving students yielded noteworthy findings, indicating that university students outperformed their managerial counterparts. Whilst acknowledging the study's limitations, these findings shed light on the relevance of logical reasoning ability in the management domain, offering valuable insights and a starting point for both researchers and practitioners.
Keywords: 650; Logical reasoning; Managerial decision making; Formal logic; Management research